2022
DOI: 10.1007/s13555-022-00709-x
|View full text |Cite
|
Sign up to set email alerts
|

Expert Consensus on the Use of Prognostic Gene Expression Profiling Tests for the Management of Cutaneous Melanoma: Consensus from the Skin Cancer Prevention Working Group

Abstract: Background: Prognostic assessment of cutaneous melanoma relies on historical, clinicopathological, and phenotypic risk factors according to American Joint Committee on Cancer(AJCC) and National Comprehensive Cancer Network (NCCN) guidelines but may not account for a patient's individual additional genetic risk factors. Objective: To review the available literature regarding commercially available gene expression profile (GEP) tests and their use in the management of cutaneous melanoma. Methods: A literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The 31-GEP test is a CM prognostic assay that measures the level of expression of 28 target genes and three control genes in order to stratify CM into low-risk (class 1A), intermediate risk (class 1B/2A), and high-risk (class 2B) categories based on risk of recurrence, metastasis and probability of sentinel lymph node biopsy (SLNB) positivity. 3 The test utilizes RNA from formalin-fixed, paraffin-embedded (FFPE) tissue samples of the primary lesion and identifies the level of expression of the 31 genes using qRT-PCR. 3 The test also adds clinical and histologic data into the GEP values to provide an integrated prognostic assessment (i31-GEP test).…”
Section: -Gep Testmentioning
confidence: 99%
See 3 more Smart Citations
“…The 31-GEP test is a CM prognostic assay that measures the level of expression of 28 target genes and three control genes in order to stratify CM into low-risk (class 1A), intermediate risk (class 1B/2A), and high-risk (class 2B) categories based on risk of recurrence, metastasis and probability of sentinel lymph node biopsy (SLNB) positivity. 3 The test utilizes RNA from formalin-fixed, paraffin-embedded (FFPE) tissue samples of the primary lesion and identifies the level of expression of the 31 genes using qRT-PCR. 3 The test also adds clinical and histologic data into the GEP values to provide an integrated prognostic assessment (i31-GEP test).…”
Section: -Gep Testmentioning
confidence: 99%
“…3 The test utilizes RNA from formalin-fixed, paraffin-embedded (FFPE) tissue samples of the primary lesion and identifies the level of expression of the 31 genes using qRT-PCR. 3 The test also adds clinical and histologic data into the GEP values to provide an integrated prognostic assessment (i31-GEP test).…”
Section: -Gep Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the development of surgical and systemic therapies [7], the survival rate of patients with SKCM remains relatively low. In terms of precision medicine, various studies have revealed that differentially expressed genes (DEGs) could be helpful in clarifying the tumor molecular biology, prognosis, and molecular targeted drugs in SKCM [8,9]. To date, a large number of biomarkers have been discovered [10][11][12], but most are in the basic research stage, and there are only a few biomarkers that can be used to guide clinical practice.…”
Section: Introductionmentioning
confidence: 99%